Quality of life of oropharyngeal cancer patients with respect to treatment strategy and p16‐positivity1. (14th November 2012) - Broglie, Martina A.; Soltermann, Alex; Haile, Sarah R.; Röösli, Christof; Huber, Gerhard F.; Schmid, Stephan; Stoeckli, Sandro J.
Abstract Objectives/Hypothesis: To assess the quality of life in long‐term survivors with oropharyngeal cancer (OPSCC), compare the results with our historic cohort in relation to the radiation technique, and explore the influence of treatment strategy and p16 expression on quality of life (QoL). Study Design: Retrospective chart analysis and patient response to EORTC QLQ‐C30 and EORTC QLQ‐H&N35 survey questionnaires. Methods: 98/120 (82%) survivors treated by primary intensity modulated chemoradiation (n = 55), or surgery with (n = 30) or without (n = 13) adjuvant radiotherapy (RT), completed and returned the questionnaires. Results: Surgically treated patients complained about significantly less troubles with dry mouth and teeth compared to the nonsurgically treated group. Comparing patients treated with surgery alone and those receiving any kind of RT (primary or adjuvant) the latter group complained about significantly more problems. Patients with p16‐positive tumors demonstrated significantly higher tumor stages, but significantly better scores in physical and role functions. Conclusions: Early disease can be treated with high long‐term QoL by surgery alone. Primary surgery with postoperative RT in selected patients with limited primary tumors and advanced neck disease renders excellent QoL. Our results suggest that IMRT is superior to former radiation techniques with regard to QoL, and should be considered as standard of care in patients undergoing RT for OPSCC. Patients with p16 positive tumors appear to show not only a better outcome but also report on a better QoL. Laryngoscope, 2013